Global prayers. Contemporary manifestations of the religious in the city. - (:unkn) unknown (L. Müller, 2014)
Religiöse Gemeinschaften schreiben sich akustisch, architektonisch, sozial und politisch in die Städte ein. Global Prayers untersucht die wechselseitigen Einflüsse von Religion und Urbanität sowie die Erscheinungsformen des Religiösen in den Metropolen der Welt. Foto-Essays, Gespräche, Reportagen, wissenschaftliche Texte und künstlerische Bildstrecken setzen sich mit der Frage auseinander, wie urbane Religion beziehungsweise religiöse Urbanität entsteht.

Religious communities inscribe themselves into the cityscape not only socially and politically, but also acoustically and architecturally. Global Prayers examines the mutual influence of religion and urbanism, looking at how various forms of faith manifest themselves in the cities of the world. Photo essays, interviews, reports, scientific texts, and artistic photo spreads inquire into the making of urban religion and the production of religious urbanity.
Keywords: Stadtsoziologie; Stadtforschung; Sozialgruppe; Kultur; Kirche; Kunst; Metropole; Religion; Multikultur